2015
DOI: 10.1080/15592294.2015.1088630
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychosocial stress during pregnancy alters the epigenetic signature of the glucocorticoid receptor gene promoter in their offspring: a meta-analysis

Abstract: Prenatal stress has been widely associated with a number of short-and long-term pathological outcomes. Epigenetic mechanisms are thought to partially mediate these environmental insults into the fetal physiology. One of the main targets of developmental programming is the hypothalamic-pituitary-adrenal (HPA) axis as it is the main regulator of the stress response. Accordingly, an increasing number of researchers have recently focused on the putative association between DNA methylation at the glucocorticoid rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 65 publications
5
114
1
4
Order By: Relevance
“…For instance, previous studies have demonstrated that higher maternal depressive symptoms during pregnancy are associated with higher mRNA levels of the glucocorticoid receptor (GR) and mineralocorticoid receptor genes in the placenta, 4 and that higher placental GR mediate the effects of maternal depressive symptoms on infant regulatory behavior. 5 Other studies have pointed to associations of maternal depression during pregnancy with epigenetic modifications of the GR gene in the placenta and fetal cord blood DNA, 3 and have found crosssectional associations between altered GR gene methylation in DNA from peripheral blood leukocytes with adolescent internalizing problems. 37 Also, higher maternal prenatal pro-inflammatory marker levels have been associated with both maternal depressive symptoms during pregnancy 6,7 and offspring autism risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, previous studies have demonstrated that higher maternal depressive symptoms during pregnancy are associated with higher mRNA levels of the glucocorticoid receptor (GR) and mineralocorticoid receptor genes in the placenta, 4 and that higher placental GR mediate the effects of maternal depressive symptoms on infant regulatory behavior. 5 Other studies have pointed to associations of maternal depression during pregnancy with epigenetic modifications of the GR gene in the placenta and fetal cord blood DNA, 3 and have found crosssectional associations between altered GR gene methylation in DNA from peripheral blood leukocytes with adolescent internalizing problems. 37 Also, higher maternal prenatal pro-inflammatory marker levels have been associated with both maternal depressive symptoms during pregnancy 6,7 and offspring autism risk.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 These symptoms may alter the intrauterine environment, expose the fetus to unnecessarily high levels of maternal glucocorticoids [3][4][5] and pro-inflammatory cytokines, 6,7 and "program" an adverse offspring phenotype, thereby explaining why maternal depressive symptoms during pregnancy predict an increased risk of psychiatric problems in the offspring. [8][9][10][11][12][13][14][15][16][17][18][19] Yet, it still remains unclear whether maternal depressive symptoms during pregnancy are an independent risk factor for child psychiatric problems.…”
mentioning
confidence: 99%
“…35 Psychosocial stress has been shown to be a risk factor for many adverse health outcomes including hypertension, 36 breast cancer, 37 and preterm birth. 38 African-Americans often endure more psychosocial stress than whites due to circumstances such as life adversity, lower socioeconomic status, discrimination, neighborhood violence, and traumatic events such as abuse or family member incarceration. 39,40 Psychosocial stress has been associated with DNA methylation as well.…”
Section: Differential Exposures and Dna Methylationmentioning
confidence: 99%
“…Subsequent human studies have confirmed exposure to childhood maltreatment and other early life adversities are associated with increased NR3C1 DNA methylation measured in both blood and post mortem brain tissue (Labonte et al, 2012; Martin-Blanco et al, 2014; McGowan et al, 2009; Tyrka et al, 2012). Maternal experiences during pregnancy have also been associated with DNA methylation differences in NR3C1 in their offspring, reviewed and summarized in a recent meta-analysis (Palma-Gudiel et al, 2015). These studies underscore the importance of early life environments and, in particular, the long-term impact of early life adversity (ELA)-induced changes to DNA methylation on mental health.…”
Section: Introductionmentioning
confidence: 99%